POVERTY DYNAMICS OF RURAL PUNJAB AND OVER TIME CHANGES - S. Akhtar; A. Saboor; A. Q. Mohsan; F. U. Hassan; A. Hussain; N. Khurshid; A. U. Khan; U. Mustafa; I. Hassan (Journal of Animal and Plant Sciences, 2015)
In Pakistan, poverty is mainly a rural phenomenon. Though poverty exists in urban areas also but rural poverty presents a bleak picture. Rural poverty varies from region to region, from one administrative division to other division.  In the history of Pakistan the persistent increase in rural poverty with few exceptions, provide enough material and raise numbers of questions in the mind of researcher. To address the issue of poverty, many of the researchers generally used secondary data to find various dimensions of poverty across regions and provinces and at the country level. In this regard very little attention was given to economically analyze the factors affecting rural poverty at divisional and district levels. The present research endeavour aimed at finding out the incidence, depth and severity of rural poverty in Punjab province. The data source for regression analysis was retrieved from Household Integrated Economic Survey (HIES) for the years 2004-05 and 2007-08.  Logit regression model was used to gauge and find out over time changes in poverty profile in rural areas of Punjab. The estimations of incidence of poverty in Punjab in the years 2004-05 and 2007-08 were 28.6 and 19.4 percent respectively. The decrease in poverty was attributed to the better economic policies of the government and the execution of development projects in the rural area particularly in the infrastructure sector. The need based development interventions keeping in view the specific measures for specific region can go a long way in alleviating poverty in rural areas of the province.
Keywords: Poverty; Alleviation; Retrieved; Logit Regression Model; Incidence